On the reliability problems of structures subjected to dynamical loads - Pho, Nguyen Van; Thach, Le Ngoc; Binh, Chu Thanh (Vietnam Journal of Mechanics, 2007)
Mechanically, the assessment of the structure’s safety relates to three aspects: strength, stability and oscillation. In the oscillation problems of structures, the safety conditions are conditions of frequency, amplitude, resonance, maximum displacement,etc ... In case that the structure itself contains random parameters and subjects to external loads that are also the random parameters (or random processes), the assessment of the structure’s safety according to the deterministic inequalities of structural mechanics will be insignificant. Therefore, this should be assessed according to the probabilistic point of view, namely, according to the reliability. The determination of reliability of the oscillation problems of structures encounters many difficulties because the outputs of the structural analysis problem are the random processes (or the random field). Meanwhile, up to now, the determination of a probability according to which a random process will belong to a given domain by mathematical method has not been sufficiently studied yet. In this paper, the authors, originating from a general definition on the reliability of a system by V. V. Bolotin, assess the reliability of oscillating structure, by determining the upper and the lower bounds of the reliability. The upper and the lower bounds of the reliability are recommended to be determined by determining the probability depending on only an inequality instead of determining the it depending on a system of inequalities. Thus, the determination is very favourable.